Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen - Nugraha, Garda Ikhsan (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
Service quality is one of the factors that can provide satisfaction to consumers. The phenomenon that occurs at Alfamart Gunung Puyuh Sukabumi City is not optimal services provided to consumers. The purpose of this study is to determine the effect of service quality on customer satisfaction in Alfamart Gunung Puyuh Sukabumi City. Data from this study are consumers of Alfamart Gunung Puyuh Sukabumi City with a population of 36,000 people. The sampling technique in this study used the Slovin formula with an error rate of 10% so that a sample of 100 respondents was obtained. Data collection techniques through questionnaire dissemination. Simple linear regression was used as an analytical technique in this study. Research findings show that there is a positive influence of service quality of 41.6% on customer satisfaction, while 58.4% is influenced by other variables that are not studied. The contribution of this study is to expand marketing management literature related to service quality and customer satisfaction in the context of organizations.